Financing Public Health in Europe - Rechel, B.; Brand, H.; McKee, M. (Das Gesundheitswesen, 2013)
The aim of this study was to ascertain the levels and mechanisms of funding public health in Europe.A review of published and unpublished documents and expenditure data was undertaken.Expenditure on public health in Europe is difficult to determine, but data from national health accounts suggest that it differs greatly across countries, both as a percentage of total health expenditure and per capita. Better data are urgently needed, given that a lack of sustainable, long-term funding may be the most significant barrier to public health programmes and interventions in Europe.In view of the current economic crisis, it will be essential to safeguard financing for public health and to put it on a more sustainable basis.
Keywords: public health; expenditure; financing; Europe